Outcome-based simulation training for ultrasound-guided central venous catheter placement: clinical impact on preventing mechanical complications - Joho Tokumine; Tomoko Yorozu; Kiyoshi Moriyama; Teruko Suzuki; Chikako Okada (BMC Medical Education)
Abstract Background Central venous catheter placement has been associated with mechanical complications, some of which can be life-threatening. Recent studies have shown that simulation-based education on ultrasound-guided central venous catheter placement improves puncture success rates; however, its effect on reducing mechanical complications remains unclear. This observational study examined how outcome-based simulation training for ultrasound-guided central venous catheter placement affects the incidence of mechanical complications in a clinical setting. Methods The Safe Central Venous Catheter Placement and Management Committee established a reporting system to monitor central venous catheter placement. In 2016, a skill assessment of ultrasound-guided central venous catheter placement was conducted. Outcome-based simulation training was introduced in 2017. Skills were evaluated using the skill assessment tool developed by the Japanese Society for Medical Simulation. Results After implementing skill assessment and outcome-based simulation training, the mechanical complication rate decreased from 2.2% in 2015 to 1.2% in 2023. Conclusions A recent meta-analysis reported a 2.3% mechanical complication rate during ultrasound-guided central venous catheter placement. In comparison, the 1.2% complication rate at our institution is notably lower. This study suggests that outcome-based simulation training for ultrasound-guided central venous catheter placement may help reduce the incidence of mechanical complications in clinical settings.